Esportes paralímpicos na educação física escolar: análise de uma intervenção - Silva, Leonardo Yoshizato (Universidade Federal de São Carlos, 2026)
This dissertation aimed to develop and analyze a didactic sequence centered on Paralympic sports in school Physical Education classes, seeking to understand what was constructed in the everyday dynamics of the lessons throughout this process. The study was conducted in a 5th-grade class at a municipal public school in Francisco Morato, São Paulo, Brazil. The class comprised 35 students, of whom 32 effectively participated in the research, adopting a qualitative approach. Data production was carried out through Field Notes written after the implementation of a didactic sequence consisting of ten 50-minute lessons, conducted between August and September 2025. The pedagogical interventions involved experiential activities with Paralympic sports such as goalball and sitting volleyball, as well as adapted games that problematized different forms of bodily participation. The theoretical framework was grounded in studies on inclusive education, the social model of disability, Paralympic sports, and School Physical Education, understanding sport as a cultural, social, and educational phenomenon. Data analysis was organized into six analytical categories: 1- “What would it be like to play without being able to see?”: the lesson begins without a ready-made answer; 2- “Too much noise”: when care becomes a condition for the game to take place; 3- “This isn’t working”: when the proposal needs to be reconstructed in the middle of the lesson; 4- “I had never noticed that”: the body as a mediator of a new reading of space; 5- “We had to change the rule”: when fairness in the game begins to be collectively constructed; and 6- “It was hard, but we managed to play”: what students come to understand about inclusion. The results indicate that inclusion did not emerge as a predefined concept, but rather as a process constructed through bodily experiences, the relationships established during the games, and the pedagogical mediations carried out throughout the didactic sequence. Experiences with goalball enabled the decentering of vision as the dominant reference, highlighting listening, silence, and care as fundamental conditions for participation. In turn, experiences with sitting volleyball and adapted games revealed that fairness in play is not limited to formal equality, but involves the collective reorganization of rules, space, and modes of participation in order to ensure real conditions for everyone’s involvement. The analyses show that students came to recognize that difficulty, fatigue, and effort do not undermine play, but rather constitute integral elements of the process of building inclusive practices. A significant shift was also observed in students’ readings of the school space, which ceased to be perceived as neutral and began to be problematized through the identification of architectural and attitudinal barriers that interfere with the participation of different bodies. Teacher mediation proved to be central to this process, as it sustained the lesson as a space for experimentation, listening, pedagogical interruption, and collective reconstruction of proposals. It is concluded that Paralympic sports, when addressed in a systematic, intentional, and contextualized manner within School Physical Education, present high educational potential, contributing to the construction of more critical, relational, and situated understandings of inclusion and participation. The study reinforces the importance of pedagogical practices that articulate bodily experience, collective reflection, and the reorganization of play, reaffirming Physical Education as a privileged space for human, social, and cultural formation.
Paralympic sport in school physical education: an analysis of an educational intervention
Keywords: Educação física escolar; Modalidades paralímpicas; Inclusão; School physical education; Paralympic sports; Inclusion; CIENCIAS DA SAUDE::EDUCACAO FISICA; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade; 10. Redução das Desigualdades